2008
DOI: 10.1159/000124380
|View full text |Cite
|
Sign up to set email alerts
|

Genomic organization, expression and evolution of porcine <i>CRSP1, 2, </i>and<i>3</i>

Abstract: Recently we identified and characterized porcine calcitonin receptor-stimulating peptide (CRSP) 1, CRSP2 and CRSP3 as members of the calcitonin/calcitonin gene-related peptide (CT/CGRP) family. In the present study, the genomic sequences and organization of CRSP1, 2, and 3 were determined, and the expression of the genes in the porcine brain was investigated using in situ hybridization. Analysis of 5′-upstream regions of the three CRSPs demonstrated that CRSP1 and CRSP2 have almost identical sequences (>98% si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…The bioinformatics gene prediction pipeline confirmed that the separate Q766Y6 and A0A761 UniProt entries are alternatively spliced variants of the same calcitonin receptor-stimulating peptide 3 ( CRSP3 ) gene as initially reported by Rezaeian et al [23]. A single genome match was identified for calcitonin receptor-stimulating peptide 2 ( CRSP2 , Q766Y7).…”
Section: Resultssupporting
confidence: 68%
“…The bioinformatics gene prediction pipeline confirmed that the separate Q766Y6 and A0A761 UniProt entries are alternatively spliced variants of the same calcitonin receptor-stimulating peptide 3 ( CRSP3 ) gene as initially reported by Rezaeian et al [23]. A single genome match was identified for calcitonin receptor-stimulating peptide 2 ( CRSP2 , Q766Y7).…”
Section: Resultssupporting
confidence: 68%
“…On the other hand, in the tetrapods lineage, CGRP gene of proto-chromosome E would tandemly duplicate and form new CGRP β gene (Figure 3 ). CRSP gene exists in the proximity of CGRP α gene on the same chromosome in the pig, horse, and dog ( 7 , 73 , 74 ). Dog CRSP gene resembles CGRP α gene in terms of generating CT mRNA by alternative splicing ( 73 ).…”
Section: Possible Evolutionary Process Of Ct/cgrp Family System From mentioning
confidence: 99%